2015
DOI: 10.1136/bjophthalmol-2015-306944
|View full text |Cite
|
Sign up to set email alerts
|

Long-term preservation of donor corneas in glycerol for keratoplasty: exploring new protocols

Abstract: Corneal tissue preserved at -80°C was the best method for preservation as it maintained the sterility, thickness, optical transparency, mechanical strength and ultrastructural features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 20 publications
1
15
0
2
Order By: Relevance
“…The use of different media to increase the shelf life of corneal buttons received at the eye bank includes the practice of recovering tissues in MK-medium with subsequent transfer to intermediate storage media. [3132] Tissue preservation in anhydrous glycerol at −80°C was found to be effective to maintain sterility of the tissue, corneal thickness, better optical transparency, tensile strength, and ultrastructural features. [32]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of different media to increase the shelf life of corneal buttons received at the eye bank includes the practice of recovering tissues in MK-medium with subsequent transfer to intermediate storage media. [3132] Tissue preservation in anhydrous glycerol at −80°C was found to be effective to maintain sterility of the tissue, corneal thickness, better optical transparency, tensile strength, and ultrastructural features. [32]…”
Section: Resultsmentioning
confidence: 99%
“…[3132] Tissue preservation in anhydrous glycerol at −80°C was found to be effective to maintain sterility of the tissue, corneal thickness, better optical transparency, tensile strength, and ultrastructural features. [32]…”
Section: Resultsmentioning
confidence: 99%
“…10 Other studies have shown that freeze-dried tissues can also be used for conditions like epikeratophakia. 11,12 Tripathi et al 7 pro-posed preserving tissues at 280°C, which maintained the sterility, thickness, optical transparency, mechanical strength, and ultrastructural features. However, there is also contradic-tory evidence suggesting that viable donor keratocytes are necessary for a successful graft until the donor graft is completely attached to the recipient cornea.…”
Section: Discussionmentioning
confidence: 99%
“…Differ-ent dehydration storage conditions have been evaluated by several research groups that include organ culture medium supplemented with 5% PEG 35,000 for the dehydration of anterior donor grafts, 6 anhydrous glycerol with and without silica gel, and various temperatures for the preservation of corneal tissues. 7 To increase the availability of these tissues, we therefore investigated if human donor corneal stroma stored in a dehydrated condition and rehydrated after 2 weeks retained the same biological and biomechanical properties. We used silica gel at room temperature as a dehydrating agent, conditions easily repeatable even in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Various reports have indicated that glycerol-dehydrated donor corneas can effectively substitute fresh corneas in patch grafts [ 21 ]. Storing corneal tissues in anhydrous glycerol at 4 °C has been shown to be as effective as storing these tissues at sub-zero temperatures [ 22 ]. Glycerol is a dehydrating agent with antimicrobial and antiprotease properties that also helps to maintain corneal structure [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%